(untitled) - Kunio, Yanagita (Tokyo, 1970)
The Object this book is mainly Yanagita Kunio and " About our Ancestors" : two kinds of meanings, a single illustration, the founder of one family, becoming an ancestor,...
Keywords: Ancestor worship,Family,Japan; Religious life and customs; Japan,Japan